Anaplastic thyroid carcinoma case series - Nadire Küçüköztaş; Tuba Taslamacıoğlu Duman; Selma Erdoğan Düzcü; Samed Rahatlı; Ümmügül Üyetürk (Northwestern Medical Journal, 2024)
Aim: Among the endocrine malignancies, thyroid carcinoma (TC) is the most common. However, anaplastic TC accounts for 1-2% of these cancers. The aim of this study was to evaluate the demographic and pathologic features, treatments, and survival of patients with anaplastic TC.